Emergency Surgery in Acute Diverticulitis: A Systematic Review. Issue 3 (March 2020) - Beyer-Berjot, Laura; Maggiori, Léon; Loiseau, Didier; De Korwin, Jean-Dominique; Bongiovanni, Jean-Pierre; Lesprit, Philippe; Salles, Nathalie; Rousset, Pascal; Lescot, Thomas; Henriot, Aymeric; Lefrançois, Magalie; Cotte, Eddy; et al.
Abstract : BACKGROUND: Acute diverticulitis is a common disease with public health significance. Many studies with a high level of evidence have been published recently on the surgical management of acute diverticulitis. OBJECTIVE: The aim of this systematic review was to define the accurate surgical management of acute diverticulitis. DATA SOURCES: Medline, Embase, and the Cochrane Library were sources used. STUDY SELECTION: One reviewer conducted a systematic study with combinations of key words for the disease and the surgical procedure. Additional studies were searched in the reference lists of all included articles. The results of the systematic review were submitted to a working group composed of 13 practitioners. All of the conclusions were obtained by full consensus and validated by an external committee. INTERVENTIONS: The interventions assessed were laparoscopic peritoneal lavage, primary resection with anastomosis with or without ileostomy, and the Hartmann procedure, with either a laparoscopic or an open approach. MAIN OUTCOME MEASURES: Morbidity, mortality, long-term stoma rates, and quality of life were measured. RESULTS: Seventy-one articles were included. Five guidelines were retrieved, along with 4 meta-analyses, 14 systematic reviews, and 5 randomized controlled trials that generated 8 publications, all with a low risk of bias, except for blinding. Laparoscopic peritoneal lavage showed concerning results of deep abscesses and unplanned reoperations. Studies on Hinchey III/IV diverticulitis showed similar morbidity and mortality. A reduced length of stay with Hartmann procedure compared with primary resection with anastomosis was reported in the short term, and in the long term, more definite stoma along with poorer quality of life was reported with Hartmann procedure. No high-quality data were found to support the laparoscopic approach. LIMITATIONS: Trials specifically assessing Hinchey IV diverticulitis have not yet been completed. CONCLUSIONS: High-quality studies showed that laparoscopic peritoneal lavage was associated with an increased morbidity and that Hartmann procedure was associated with poorer long-term outcomes than primary resection with anastomosis with ileostomy, but Hartmann procedure is still acceptable, especially in high-risk patients. Abstract : Supplemental Digital Content is available in the text.